(untitled) (Journal of Engineering, 2023)
When a vehicle is left parked in the sun for an extended period, the gathered heat causes damage to several interiors within the cabin and causes discomfort for people and animals left inside the car. In the present work, the effect of the orientation of a parked white minibus on temperature distribution and cooling load calculation is studied experimentally in an open environment. Two different cases were studied facing south and facing east. For several hours, the temperature inside the car cabin had been monitored and measured at five separate locations. The cooling load calculations are carried out based on the experimental measurements. The results show that the overheating of parked cars always happens as a result of the radiation load especially when a car has a large surface glass area. Also, the ambient load is directly proportional to the ambient temperature, and the total load related directly to radiation load reaches the maximum value of 2358.1 W at 3:00 pm for 1st case and 2118.3 W at 11:00 am for 2nd case which shows an increase of 11.32 %. Thus, these results emphasized the fact that the orientation of the parked car may considerably affect the temperature distribution and the cooling load of the car cabin. Also, the study may be considered an essential step in designing any assisted ventilation or auxiliary air conditioning system that may enhance the car cabin conditions even while the car’s engine was off (parked automobile).